A Consensus-Based Distributed Secondary Control Optimization Strategy for Hybrid Microgrids - Espina-Gonzalez, E (Institute of Electrical and Electronics Engineers Inc., 2023)
In this paper, a new consensus-based distributed secondary control (DSC) strategy is proposed for frequency control, dc -voltage regulation, and optimal dispatch (OD) in isolated hybrid ac/dc - microgrids (HMGs). At the same time, all the units are maintained within limits. The proposed control scheme dispatches the distributed generators (DGs) within the microgrid in compliance with the Karush-Kuhn-Tucker (KKT) conditions of a linear optimal power flow (OPF) formulation. Furthermore, the power through the interlinking converters (ICs) is also dispatched to help minimize the total operation cost of the microgrid. The controllers rely on local measurements and information from neighbouring devices at both sides of the microgrid (DGs and ICs). Thus, unlike conventional methods, the microgrid is considered a single entity and not as three independent systems interacting with one another, and the OD is calculated considering both the ac -DGs and dc -DGs. Extensive simulations demonstrate a good performance of the controller amid load step changes and unit congestion, driving the system to an optimal economic operation. © 2010-2012 IEEE.